2020
DOI: 10.1007/s00784-020-03275-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, two-month pilot trial of stannous fluoride dentifrice versus sodium fluoride dentifrice after oxalate treatment for dentinal hypersensitivity

Abstract: Objectives To compare the effects of a stannous fluoride dentifrice and a sodium fluoride dentifrice on dentinal hypersensitivity when used with an oxalate-based regimen combining in-office and at-home treatment. Materials and methods In this single-center, randomized, controlled, double-blind, pilot clinical trial, 30 subjects were professionally treated at baseline with a 3% oxalate/potassium salt solution on up to two target teeth, then randomized 1:1 to either 0.454% stannous fluoride or 0.243% sodium fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Historically, various approaches, such as calcium-containing pastes (Pei et al, 2013), sodium fluoride (Anderson et al, 2020), and laser treatment (Meng et al, 2023), have been used for tubule obstruction, but limitations persist, including shallow infiltration and the susceptibility to re-exposure during acid attack (Wang et al, 2010). Beltrame et al (2018) reported a 28% reduction in EDL with phosphorylated chitosan after 5 days of acid erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, various approaches, such as calcium-containing pastes (Pei et al, 2013), sodium fluoride (Anderson et al, 2020), and laser treatment (Meng et al, 2023), have been used for tubule obstruction, but limitations persist, including shallow infiltration and the susceptibility to re-exposure during acid attack (Wang et al, 2010). Beltrame et al (2018) reported a 28% reduction in EDL with phosphorylated chitosan after 5 days of acid erosion.…”
Section: Discussionmentioning
confidence: 99%
“…The oral pH levels depend upon the individual’s eating habits, oral hygiene practices, fluoride usage, and the composition and the quality of saliva and plaque [ 43 ]. For this reason, further in vitro studies and especially clinical trials are needed to validate the promising outcome of this research and clinically evaluate the remineralization efficacy of RA [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned theory is the most acceptable theory based on the dynamic flow of dentinal fluid [ 4 ]. Usually, when dentin tubules are exposed to the external environment, different stimuli can make the fluid in dentin tubules to move, which leads to nerve fiber stimulation and pain [ 5 ]. The cause of tubule exposure is multi-factorial.…”
Section: Introductionmentioning
confidence: 99%